Evaluating China’s urbanization trajectory: an overextension or still in progress? - Wei, Yujun; Yuan, Fan; Ye, Zhonghua (Frontiers in Environmental Science, 2024)
China’s urbanization has undergone a transformative journey since the initiation of the reform and opening-up policy in 1978, catalyzing economic growth while profoundly impacting its ecological and demographic landscapes. This study offers a systematic evaluation of China’s urbanization trajectory over the past 4 decades through the development of an indicator system encompassing three key dimensions: population urbanization, land urbanization, and economic urbanization. Using the entropy method for weight assignment, the analysis reveals a consistent upward trend in China’s comprehensive urbanization, with occasional sharp increases. Although population urbanization influences the overall index, land urbanization has outpaced both population and economic urbanization, indicating a pronounced dependence on land resources. This trend poses a potential risk of unsustainable urban growth if left unaddressed. The findings indicate that to achieve sustainable urban development, China must prioritize balancing the interplay between population and land, moving away from land-dependent strategies, and adopting a more balanced approach to urbanization. The quantitative analysis provides key insights into this imbalance, indicating that policies should integrate land use planning with population dynamics to promote holistic urban growth. Future research should investigate the long-term socio-economic and environmental impacts of land-centric urbanization and propose innovative strategies to guide China towards a sustainable urban future.